STUDI EFEKTIVITAS PELAYANAN PUBLIK DI KECAMATAN KEJAKSAN KOTA CIREBON - Layaman, Layaman; Hartati, Suci (Universitas Muhammadiyah Surakarta, 2008)
This research early from problem not yet is effective officer service of district government in giving public service to society. Proven by existence ofunjust service and delay of arrangement of work, the problem arise because of less its discipline of district government officer and less supporting climate work inarrangement of work. Based on the problem, writer conduct the research with use methode of survey with data collecting technique there are use to bibliographydata, observation, interview and spreading a set questionnaire. The objective of the research were to review and to analyze a relation of discipline work and climate work to effectiveness service of government officer in District of Kejaksan, Town of Cirebon. Hypothesis which writer raise there are (1) There is influence of discipline work government officer of district to service effectiveness, (2) There is influence of work climate to service effectiveness. This research used to doubled linear regression analysis. Based on the result of solution and analysis concerning Influence of discipline work and climate work in District of Kejaksan, Town of Cirebon there are (1) Discipline work an climate work government officer District of Kejaksan it can be good categorized. That is it can be seen from responder answer which majority answer agree. The result of analysis of regression also show the existence of influence which are positive from both variable to effectiveness service public,(2) Variable ofworking discipline (X1) and organizational climate always influence effectiveness service of public in District of Kejaksan, Town of Cirebon. And that 65,1%effectiveness service of public can be explaines by discipline work variable and work climate variable, while the rest 34,9% explained by other causes which there are not yet to check, and then (3) By parsial analize, discipline work and organizational climate have influence to effectiveness service of public.